A game theoretic approach of optimal adoption time of blockchain: A case of ship operators. (July 2022) - Pu, Shuyi; Lam, Jasmine Siu Lee
Highlights: A game-theoretic model is developed considering multiple competing ship operators. A novel algorithm is proposed to solve the numerical Nash equilibrium. A mixed pricing model achieves faster and wider blockchain adoption. Substitution policy only threatens small operators under a fixed pricing model. Blockchain's cost-effectiveness is crucial to advance blockchain adoption. Abstract: With increasing uncertainties in the global economy, companies are facing fierce competition. Blockchain has the potential to enhance companies' competitiveness by streamlining processes, improving productivity and reducing costs. It is meaningful to study whether and when companies would adopt blockchain and under what conditions. We develop a game theoretic model to analyse the introduction of blockchain to companies from a big customer with bargaining power. In this study, ship operators need to decide their optimal adoption time when facing a request from a big shipper to adopt blockchain with a threat of substitution policy from the shipper. An algorithm is developed to obtain the numerical solutions of ship operators' optimal adoption time. Our analysis suggests that 1) the substitution policy only matters to small companies and is only necessary under fixed pricing model; 2) a threshold applies for substitution ratio and cut-off time to effectively induce small companies to adopt blockchain early; 3) blockchain developers should consider mixed pricing model instead of fixed pricing model for faster and wider blockchain adoption; 4) blockchain initiators should focus more on improving the technology's cost-effectiveness rather than rely heavily on externalities like substitution policies to promote blockchain adoption.